PRPF19 modulates morphology and growth behavior in a cell culture model of human skin - Kleissl, Lisa; Weinmüllner, Regina; Lämmermann, Ingo; Dingelmaier-Hovorka, Ruth; Jafarmadar, Mohammad; El Ghalbzouri, Abdoelwaheb; Stary, Georg; Grillari, Johannes; Dellago, Hanna (Frontiers in Aging, 2023)
The skin provides one of the most visual aging transformations in the human organism, and premature aging as a consequence of oxidative stress and DNA damage is a frequently seen effect. Cells of the human skin are continuously exposed to endogenous and exogenous DNA damaging factors, which can cause DNA damage in all phases of the cell cycle. Increased levels of DNA damage and/or defective DNA repair can therefore accelerate the aging process and/or lead to age-related diseases like cancer. It is not clear yet if an enhanced activity of DNA repair factors could increase the life or health span in cells of the human skin. In previous studies we identified and characterized the human senescence evasion factor (SNEV)/ pre-mRNA-processing factor (PRPF) 19 as a multitalented protein involved in mRNA splicing, DNA repair pathways and life span regulation. Here we show that the overexpression of PRPF19 in human dermal fibroblasts leads to a morphological change, reminiscent of juvenile, papillary fibroblasts, despite simultaneous expression of senescence markers. Moreover, conditioned media of this subpopulation showed a positive effect on keratinocyte repopulation of wounded areas. Taken together, these findings indicate that PRPF19 might be able to promote cell viability and slow down the aging process in human skin.